A fission yeast cell-based system for multidrug resistant HIV-1 proteases. Issue 1 (December 2017) - Benko, Zsigmond; Liang, Dong; Li, Ge; Elder, Robert; Sarkar, Anindya; Takayama, Jun; Ghosh, Arun; Zhao, Richard
Abstract Background HIV-1 protease (PR) is an essential enzyme for viral production. Thus, PR inhibitors (PIs) are the most effective class of anti-HIV drugs. However, the main challenge to the successful use of PI drugs in patient treatment is the emergence of multidrug resistant PRs (mdr PRs). This study aimed to develop a fission yeast cell-based system for rapid testing of new PIs that combatmdr PRs. Results Threemdr PRs were isolated from HIV-infected patients that carried seven (M7 PR), ten (M10 PR) and eleven (M11 PR)PR gene mutations, respectively. They were cloned and expressed in fission yeast under an inducible promoter to allow the measurement of PR-specific proteolysis and drug resistance. The results showed that all threemdr PRs maintained their abilities to proteolyze HIV viral substrates (MA↓CA and p6) and to confer drug resistance. Production of these proteins in the fission yeast caused cell growth inhibition, oxidative stress and altered mitochondrial morphologies that led to cell death. Five investigational PIs were used to test the utility of the established yeast system with an FDA-approved PI drug Darunavir (DRV) as control. All six compounds suppressed the wildtype PR (wt PR) and theM7 PR-mediated activities. However, none of them were able to suppress theM10 PR or theM11 PR. Conclusions The three clinically isolatedmdr PRs maintained their viral proteolytic activities and drug resistance in the fission yeast. Furthermore, those viralmdr PR activities were coupled with the induction of growth inhibition and cell death, which could be used to test the PI activities. Indeed, the five investigational PIs and DRV suppressed thewt PR in fission yeast as they did in mammalian cells. Significantly, two of the high levelmdr PRs (M10 PR andM11 PR) were resistant to all of the existing PI drugs including DRV. This observation underscores the importance of continued searching for new PIs againstmdr PRs.